(untitled) (Palíndromo, 2025)
This article calls attention to the exhibition Tiempo de Mirar: visita virtual a las obras perdidas en el incendio en Rio de Janeiro, held at the Museo Torres-García in 2018, and its expography. It also studies some of the fragments displayed at the exhibition. In July 1978, the Rio de Janeiro’s Museum of Modern Art suffered a tragic fire that destroyed several works of art, including 74 works - paintings, sculptures, and toys - made by Joaquín Torres-García, a Uruguayan artist whose works were, numerically, the most affected. Tiempo de Mirar reintroduced these destroyed works of art to the public, via augmented reality. The visitants could access them through the smartphone camera by pointing at the QR Codes on the walls. The exhibition also presented Torres-García’s artworks fragments that were severely damaged by the fire but not destroyed, making absence and presence coexist in the same place, and provoking a remembrance process.